PARADIGM OF ECOTOURISM-BASED TOURISM DEVELOMENT IN CONTEXT OF REGIONAL ECONOMIC DEVELOPMENT ACCELERATION - Syaparuddin Syaparuddin; Dearmi Artis (LPPM UNIMAL, 2018)
This research aims at analizing the progress of tourism sector development in Indonesia in relation to regional development dinamics and to analize tourism sector development model integratively. Analisys model used in this research is qualitative descriptive method. Coverage of analisys are the area which have tourism potetials or main tourism destination in Indonesia, having ability to develop rapidly. The progress of tourism will certainly accelerate regional development including its regional economy. The model of integrative ecotourism development can be applied by sinergizing regional andcentral government, as well as private sector and society in the frame of developing main infrastructure and its supporting facilities, human resources and ecotourims management.